PROBLEMATIKA PERLINDUNGAN TERHADAP KONSUMEN PAKAIAN BEKAS - DHEA ANANDA ADAM; NIRWAN JUNUS; JULIUS T. MANDJO; MUHAMAD KHAIRUN KURNIAWAN KADIR; KARLIN Z. MAMU (Universitas Mahasaraswati K. Mataram, 2024)
This research aims to determine the problems of protecting consumers of imported used clothing. This research uses empirical legal research methods with a case approach that occurs, then analyzed using descriptive analytical techniques. The research results show that basically consumer protection against the sale of imported used clothing in Gorontalo in terms of Law Number 8 of 1999 is carried out by providing guidance to the Non-Governmental Consumer Protection Institution (LPKSM). Carrying out law enforcement efforts through preventive actions such as raids and visiting sales centers, including checking procedures and business permits, especially buying and selling clothes and site construction permits. Apart from that, it provides warnings to business actors who then take action with confiscation and provide sanctions for perpetrators who are still unaware. However, even though there are regulations that prohibit imported used clothing, this business tends to still have a lot of interest. This law enforcement effort is carried out by coordinating with Civil Servant Investigator Supervisors (PPNS) for Consumer Protection from Regency and City to the Police, as well as goods and services supervisors. The problem of providing protection to consumers of imported used clothing in Gorontalo City is that there is a strong desire that arises in sellers and buyers; New law enforcement is limited to socialization and appeals, without confiscation and imposing sanctions; There are no regional regulations in the form of regional regulations; and Lack of Public Awareness.